Prevalence and Pattern of Hypoxic Ischemic Encephalopathy in Pediatric Patients Analysis by MRI Assistance (Medical Forum Monthly, 2023)
Objective: To examine the prevalence and pattern of hypoxic-ischemic encephalopathy (HIE) in pediatric patients.Study Design: A retrospective cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Pediatrics, Bacha Khan Medical Complex from July 2022-January 2023.Materials and Methods: Our study included children from newborns to 16 years of age who either had a history of fits, abnormal APGAR score, delayed cry or delayed milestones. The brain MRI was performed on 1.5 tesla scanner with a standard protocol and interpreted by Experienced Radiologists Findings were recorded and data was analyzed on SPSS version 26. Children who were born via instrumental delivery were excluded from our study. A total of 50 pediatric patients from newly born to 16 years old with HIE were included.Results: The overall prevalence of HIE was 28%. Mild to moderate HIE was the most prevalent pattern, accounting for 19% of the cases. The most common pattern of injury was global (14%), followed by focal (12%) and multifocal (2%). The most common affected areas were the basal ganglia, thalamus, and cortical white matter. The results showed that HIE was 28% with the majority of cases being moderate to mild. The most common injury pattern was global, followed by focal and multifocal.Conclusion: Hypoxic Ischemic Encephalopathy is a common occurrence in our society and MRI is the recommended modality due to its sensitivity and superior soft-tissue resolution. In developing countries due to a lack of proper facilities and awareness, there is an increased incidence of HIE which leads to increased morbidity therefore increasing awareness and early diagnosis is of utmost importance. The most common injury pattern was global, followed by focal and multifocal, with the most affected areas being the basal ganglia, thalamus, and cortical white matter.